Petri net-based approach for web service automation resource coordination - Mendes, João M. (2018)
In industrial automation, control systems and mechatronic devices are from diverse nature, supplied by different manufacturers and made of different technologies. The adoption of web services principles in an automated production system satisfies some requirements, namely the interoperability of such heterogeneous and distributed environments and the basis for flexibility and reconfigurability. Manufacturing processes require to access resources at different precedence levels and time instances, but in the other way resources may also be shared by different processes. A major challenge is then how individual services may interact, coordinating their activities. Petri nets may be used to describe complex system behaviour and therefore also applied to coordinate such systems. The paper introduces a Petri net based approach for the design, analysis and coordination of systems developed using web services to represent individual and autonomous resources. For this purpose, it is presented a Petri nets computational tool to support the design, validation and coordination of web service based automation systems.